CHINA – CAMBODIA RELATIONSHIPS: PHNOM PENH as BEIJING’S PERMANENT CLIENT STATE - Sigit Candra Wiranata Kusuma (President University, 2019)
The purpose of this paper is to analyze the relationship between Cambodia and People’s Republic of China (PRC)use historical approach and secondary data regarding the topic. Although Cambodia and PRC do not share direct border, their relationship has been flourished since Cambodia gaining their independence from France in 1953 under the regime of Norodom Sihanouk until the administration of Prime Minister Hun Sen. Since then, China has been injecting Cambodia with financial aids, which helping Cambodia to establish its nation. Noting the power gap between two nations that would be complicate the relationships between two. In addition, China with its famous five peaceful coexistence has managed to build closer ties with Cambodia. This paper concluded thatafter the implementation of Belt and Road Initiative(BRI)in 2013, the relationship began to shift from China’s closest friend in Southeast Asia towards something beyond diplomatic ties, which is Cambodia as a permanent client state of PRC and has strong normative background, and the ties itself invites many critics both from regional and international. For instance, during the Disputes of South China Sea and 45th ASEAN annual meeting where Cambodia shown their firm positions in line with China. Cambodia is appeared to show its loyalty to China as a form of payback for years of Chinese financial aids and investment for decades.Keywords:Sino-Khmer ties, BRI, Chinese permanent client, and Development of Cambodia